Праця як соціальне підприємництво та її інтерпретація сучасним богослов'ям - Кулагіна-Стадніченко, Г. (Київський національний університет імені Тараса Шевченка, 2018)
У цій статті авторка вказує на те, що економічна криза може викликати не лише спалах аморальності, а й відтворити ті сили суспільства, які можуть протистояти цьому. Надія на авторитетного лідера здорових сил суспільства часто покладається на релігію. Дослідниця стверджує, що на відміну від багатьох інших релігій та філософських вчень, християнство визнає благом матеріальний, видимий світ. Зневажливому ставленню до людей праці християнство протиставляє повагу до них. У християнстві активність, творчість, праця сприймаються як беззаперечна цінність. У праці виявляється високе покликання людини – за словами Орігена: "Бог створив людину істотою, що потребує праці". Разом з тим, праця аналогічна покаранню – Тома Аквінський називає її "важким благом". У статті авторка доводить, що така антиномічність має богословське пояснення. У висновку дослідниця зауважує, що всі християнські конфесії прагнуть відповісти на актуальні питання сучасного суспільного життя, почасти вони виступають спільником держави у розв'язанні складних проблем сьогодення. Авторка вказує на важливість активної громадянської позиції конфесій, яка постає необхідною передумовою толерантних державно-церковних відносин цивілізованого суспільства.

In this article the author points out that the economic crisis can cause not only the outbreak of immorality, but also recreate the forces of society that can withstand this. Hope for the authoritative leader of the healthy forces of society often relies on religion. The researcher argues that, unlike some other religions and philosophical doctrines, Christianity recognizes the material world and does not despise people of labor. In Christianity, activity, creativity and work are perceived as an indisputable value. According to Origen: "God created man as a creature who needs in labor". At the same time, work is similar to punishment – Toma Aquinas calls it a "hard blessing". In the article, the author argues that such antinomy has a theological explanation. In modern science, labor ethics is determined by a set of norms, values that people and groups of people have in relation to work. Labor is understood as mental or physical, intense, paid or unpaid activity, whose purpose is the production of goods and services useful to society, which can be produced under conditions of industrial or consumer economics. The duty to work is the task of everyone who is able to work. In addition to the duty to work, the right to work is defined, which is defined as the right to receive and retain a work place. In the sense of the individual right to work provided by the state, the right to work in Ukraine is not protected at present. However, it is relevant as a task for central authorities, namely, as their duty to achieve full employment of the population of the society. The desire to find ways to get out of the "deadlock" has led Catholic theologians to develop the concept of "middle system", which is an integral part of the Catholic social doctrine. The central place in the papal social document is the principle of subsidiarity, which has a different name – the principle of competence. It answers the question of which individuals, groups, communities, institutions take care of the relevant economic, social actions. At the same time as the reform of society, the main objective of the Encyclical Quadragesimo anno (1931) was the reform of the style of thinking. Thus, the encyclical serves as a social document that directs to the "third way". This means that uncontrolled freedom of competition, which was the most significant cause of a social problem, should be governed by a regulatory principle. In other words, on the agenda – the planning and management of the economy, which need to be institutionalized. In conclusion, the researcher notes that all Christian denominations seek to answer the urgent problems of modern social life, and in part they act as an accomplice of the state in solving complex problems of our time. The author points out the importance of active civic position of denominations, which is an important prerequisite for tolerant state-church relations of a civilized society.
The work as a social enterprise and its interpretation by the modern theology
Keywords: "витрати" початкового накопичення капіталу; християнська етика праці; обов'язок до праці; право на працю; енцикліки; принцип субсидіарності (компетентності); "expenses" of initial accumulation of capital; Christian ethics of labor; duty to work; the right to work; encyclicals; the principle of subsidiarity (competence)